Lizy

\(x^2+\dfrac{9x^2}{\left(x-3\right)^2}=40\)

ĐKXĐ: x<>3

\(x^2+\dfrac{9x^2}{\left(x-3\right)^2}=40\)

=>\(\dfrac{x^2\left(x-3\right)^2+9x^2}{\left(x-3\right)^2}=40\)

=>\(x^2\left(x^2-6x+9+9\right)=40\left(x-3\right)^2\)

=>\(x^4-6x^3+18x^2=40\left(x^2-6x+9\right)\)

=>\(x^4-6x^3+18x^2-40x^2+240x-360=0\)

=>\(x^4-6x^3-22x^2+240x-360=0\)

=>\(\left(x-2\right)\left(x+6\right)\left(x^2-10x+30\right)=0\)

mà \(x^2-10x+30=x^2-10x+25+5=\left(x-5\right)^2+5>=5>0\forall x\)

nên (x-2)(x+6)=0

=>\(\left[{}\begin{matrix}x=2\left(nhận\right)\\x=-6\left(nhận\right)\end{matrix}\right.\)

Bình luận (0)
Nguyễn Việt Lâm
3 tháng 4 lúc 22:17

ĐKXĐ: \(x\ne3\)

\(\Leftrightarrow x^2+\left(\dfrac{3x}{x-3}\right)^2+2x.\dfrac{3x}{x-3}-2x.\dfrac{3x}{x-3}=40\)

\(\Leftrightarrow\left(x+\dfrac{3x}{x-3}\right)^2-2x.\dfrac{3x}{x-3}=40\)

\(\Leftrightarrow\left(\dfrac{x^2}{x-3}\right)^2-6.\dfrac{x^2}{x-3}=40\)

Đặt \(\dfrac{x^2}{x-3}=t\)

\(\Rightarrow t^2-6t-40=0\Rightarrow\left[{}\begin{matrix}t=10\\t=-4\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}\dfrac{x^2}{x-3}=10\\\dfrac{x^2}{x-3}=-4\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x^2=10x-30\\x^2=-4x+12\end{matrix}\right.\) 

\(\Rightarrow\left[{}\begin{matrix}x^2-10x+30=0\\x^2+4x-12=0\end{matrix}\right.\) (bấm máy)

Bình luận (0)

Các câu hỏi tương tự
Dung Vu
Xem chi tiết
Thanh Thanh
Xem chi tiết
Lee Yeong Ji
Xem chi tiết
Dung Vu
Xem chi tiết
Hoàng Phú Lợi
Xem chi tiết
Hoàng Phú Lợi
Xem chi tiết
Lương Ngọc Anh
Xem chi tiết
Nguyễn Tấn Thịnh
Xem chi tiết
ARMY MINH NGỌC
Xem chi tiết
Lấp La Lấp Lánh
Xem chi tiết